International development studies theories and methods in research and practice - Sumner, Andrew 1973-
This text is concerned with what constitutes knowledge in development studies and how it is created, and is intended as a teaching text on methodology and epistemology in development studies as well as being a contribution to contemporary debates on the nature of the discipline